In silico characterization of functional single nucleotide polymorphisms of folate pathway genes. (25th March 2018) - Vohra, Manik; Sharma, Anu Radha; Paul, Bobby; Bhat, Manoj K; Satyamoorthy, Kapaettu; Rai, Padmalatha S.
Abstract: Folate metabolism genes are pivotal to critical biological processes and are related to several conditions, including developmental, cognitive, and cardiovascular anomalies. A systematic catalog of genetic polymorphisms in protein coding regions, regulatory transcription factor binding sites, and miRNA binding sites associated with folate pathway genes may contribute to personalized medicine. We performed a comprehensive computational survey of single nucleotide polymorphisms (SNPs) of folate pathway genes to highlight functional polymorphisms in the coding region, transcription factor binding sites, and miRNAs binding sites. Folate pathway genes were searched through PubMed and Kyoto Encyclopedia of Genes and Genomes pathway databases. SNPs were identified and characterized using the University of California, Santa Cruz genome browser and SNPnexus tool. Functional characterization of nonsynonymous SNPs (nsSNPS) was performed using bioinformatics tools, and common deleterious nsSNPs were identified. We identified 48 genes of folate pathway containing 287 SNPs in the coding regions. Out of these SNPs, rs5742905, rs45511401, and rs1801133 were predicted to be deleterious through four different bioinformatics tools. Three‐dimensional structures of two proteins with and without deleterious nsSNPs were predicted by SWISSPDB viewer and SuperPose. Besides, a total of 237 SNPs was identified in transcription factor binding sites using the Genomatix software suite and six miRNA target site SNPs using miRNASNP. This systematic and extensive in silico analysis of functional SNPs of folate pathway may provide a foundation for future targeted mechanistic, structure‐function, and genetic epidemiological studies.